Review the impact of outdoor environment and the quality of life - Eusuf, Muhammad Abu; Mohit, Mohammad Abdul; Sami Eusuf, MMR; Ibrahim, Mansor (2014)
The features of outdoor environment in urban spaces and morphology affect the quality of life (QoL) of urban inhabitants and visitors. The aim of this study is to develop an extensive supposition on the parametric valuation related to the modification of the urban environment and inhabitant’s QoL by thorough literature review, field observation and proposal on an alternative design strategy. The parameters include microclimatic conditions, urban space and traffic, waste minimization and other factors influences are needed to consider for intensive investigation. Its play a key role on the modification of QoL and directly affects the dweller attitude and behaviour.